The utility of innominate dry bone weight in age estimation: A new pelvic aging method - Andrea M. Zurek-Ost; Mark Sorensen (PLoS ONE, 2026)
This research investigated the relationships between bone weight, chronological age, and biological sex. This study examined 383 innominates from individuals aged 16–93 years to investigate how bone weight (here a proxy for bone mineral density) was patterned throughout the lifespan. Standard osteology laboratory equipment as well as a scale were used to measure innominate height and dry bone weight. Dry bone weight is an imperfect proxy for bone mineral density; however, the phenomenon of decreases in bone weight with age was observed and quantified in this dry bone sample. While both males and females are affected by a slow reduction in bone mineral density over the course of their lifespans, this effect is exaggerated in females and was reflected in the study results. To quantify these changes, the authors created predictive Bayesian linear models to estimate age at death from dry bone weight, height, and biological sex. The best performing model R 2 was 0.33, with an average inaccuracy of 9.37 years. Estimated age was within ±10 years of known age for 57.3% of the training sample, and 87.2% of estimated ages at death were within ±20 years of known age. When these models were tested on a smaller modern subsample, the results were both less accurate and less precise, demonstrating a need for validation on expanded modern samples. Overall, these results demonstrate that significant decreases in dry bone weight are associated with increased chronological age in the training sample, particularly in females. This study demonstrates that dry bone weights may be used to support estimates of chronological age; however, they should be applied cautiously, further tested, and only used in concert with well-validated age-at-death estimation methods.